Recommended Actions of the ACAP Report on the Reduction of Black Carbon Emissions from Residential Wood Combustion. - Arctic Contaminants Action Program (ACAP) (ACAP Secretariat, 2015)
This pamphlet presents key findings from an Arctic Contaminants and Action Program (ACAP) project to identify actions that can contribute to reducing emissions of black carbon (BC) from residential wood combustion in the pan-Arctic region. Nominated experts from Canada, Denmark, Finland, Norway, Sweden and the USA have worked together and shared their national data and expertise on BC emissions inventories and their experience with various black carbon abatement instruments and measures. Their contributions and expertise are compiled and expressed throughout the full data analysis, discussions and recommendations of the ACAP report. SINTEF; Norsk Energi